Cognitive Consequences of Iodine Deficiency in Adolescence: Evidence from Salt Iodization in Denmark - Benjamin Ly Serena (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2019)
Over the past three decades, many countries have introduced iodized salt policies to eradicate iodine deficiency. While it is well known that iodine deficiency in utero is detrimental to cognitive ability, little is known about the consequences of iodine deficiencies after birth. This paper examines the impact of iodine deficiency in adolescence on cognitive performance. I identify the causal effect of iodine deficiency quasi-experimentally using the introduction of iodized salt in Denmark. Denmark went from a ban on iodized salt before 1998 to a mandate after 2001, making it an ideal national experiment. Combining administrative records on high school grades over a thirty-year period with geographic variation in initial iodine deficiency, I find that salt iodization increases the Grade Point Averages of high school students by 6-9 percent of a standard deviation. This improvement is comparable to the benefits of more standard school achievement policies and at much lower costs.
Keywords: I15; I18; J24; 330; Iodine Deficiency; Iodized Salt; Nutrition; Human Capital; Health